2020
DOI: 10.1186/s12889-020-09609-1
|View full text |Cite
|
Sign up to set email alerts
|

El Niño Southern Oscillation as an early warning tool for dengue outbreak in India

Abstract: Background Dengue is rapidly expanding climate-sensitive mosquito-borne disease worldwide. Outbreaks of dengue occur in various parts of India as well but there is no tool to provide early warning. The current study was, therefore, undertaken to find out the link between El Niño, precipitation, and dengue cases, which could help in early preparedness for control of dengue. Methods Data on Oceanic Niño Index (ONI) was extracted from CPC-IRI (USA) while the data on monthly rainfall was procured from India Mete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
(44 reference statements)
0
6
1
Order By: Relevance
“…These findings diverge from previous research that mainly focused on the positive correlation between dengue outbreaks and El Niño, the warming phase of ENSO ( Vincenti-Gonzalez et al, 2018 ; Xiao et al, 2017 ; Pramanik et al, 2020 ). The contrast in our results underscores the complexity of the relationship between ENSO and dengue infections, indicating that different ENSO phases may have varying effects on dengue transmission dynamics.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings diverge from previous research that mainly focused on the positive correlation between dengue outbreaks and El Niño, the warming phase of ENSO ( Vincenti-Gonzalez et al, 2018 ; Xiao et al, 2017 ; Pramanik et al, 2020 ). The contrast in our results underscores the complexity of the relationship between ENSO and dengue infections, indicating that different ENSO phases may have varying effects on dengue transmission dynamics.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, studies in Curaçao ( Limper et al, 2010 ; Limper et al, 2016 ) and Guadeloupe ( Gharbi et al, 2011 ) identified a decrease in mean temperature to be related to more dengue cases. Relevant to this aspect is the occurrence of El Niño Southern Oscillation (ENSO), as there are multiple studies ( Vincenti-Gonzalez et al, 2018 ; Xiao et al, 2017 ; Pramanik et al, 2020 ) that revealed a link between dengue and the warming phase of ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme prolonged climatic events can also drive the potential for dengue transmission by influencing human behavior, such as droughts that may result in people increasing water storage practices that could serve as breeding grounds for mosquitos [ 77 ]. Broader climate phenomena such as sea surface temperature or Oceanic Niño Index, can influence weather patterns (i.e., changing temperature or precipitation), and depending on the geography can further contribute towards localized impacts as mentioned, thereby altering transmission dynamics [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…ENSO-related climate variability is also a known driver of the emergence and outbreaks of infectious diseases [ 3 , 10 ]. Outbreaks of numerous infectious diseases, such as cholera [ 11 ], Rift Valley fever [ 12 ], visceral leishmaniasis [ 13 ], dengue [ 14 , 15 ], Zika virus [ 16 ], and malaria [ 17 ], among others, have been linked to the ENSO. The emergences of some viral diseases of bat origin, such as the Hendra virus (HeV) in Australia and the Nipah virus (NiV) in Malaysia, have also been associated with El Niño events [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%